2019
DOI: 10.1021/acs.jpcc.9b06119
|View full text |Cite
|
Sign up to set email alerts
|

Descriptor for the Efficacy of Aliovalent Doping of Oxides and Its Application for the Charging of Supported Au Clusters

Abstract: We have studied aliovalent doping of oxides, which is central to many applications in technology, using density functional theory (DFT). We consider the following anionic/cationic donor/acceptor dopants in MgO: Al, F, N, P, Li, Na, and K. Not all dopants donate or accept charge to the full extent expected from their nominal oxidation state. Counterintuitively, the charge accepted/donated by a dopant is found to not scale with Δχ alone, where Δχ is the difference in electronegativities between the anion/cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 125 publications
1
11
0
Order By: Relevance
“…Ag, Nb, and Ru formed direct bonds to NO 2 during all optimization attempts, so their binding energies were excluded from the data set so that only surface-mediated effects were considered. Doping the oxide surface alters the electronic structure of the oxide in a manner similar to the adsorbates 37,39,[44][45][46] . Li, Na, B, and Al were chosen as dopants in this study, as they contain either one fewer or one additional valance electron compared to Mg.…”
Section: Effects Of Dopants and Adsorbates On Metal Adsorption Energymentioning
confidence: 99%
See 2 more Smart Citations
“…Ag, Nb, and Ru formed direct bonds to NO 2 during all optimization attempts, so their binding energies were excluded from the data set so that only surface-mediated effects were considered. Doping the oxide surface alters the electronic structure of the oxide in a manner similar to the adsorbates 37,39,[44][45][46] . Li, Na, B, and Al were chosen as dopants in this study, as they contain either one fewer or one additional valance electron compared to Mg.…”
Section: Effects Of Dopants and Adsorbates On Metal Adsorption Energymentioning
confidence: 99%
“…Adsorbates from the reaction environment, or dopants present in the oxide structure, can enhance charge transfer at the metal/ support interface 31,[36][37][38][39][40] . Addou et al 41 demonstrated that adsorbed hydrogen atoms on the rutile TiO 2 (011)-(2 × 1) surface alters the binding energy of Pd atoms to the support, which stabilizes small Pd n clusters (i.e., n~1-3 atoms).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Subsequently, we showed that similar wetting transitions are also observed at other cluster sizes. 59 Next, we considered the question of which dopants might be the most effective in tuning the charge of the cluster; in this previous study, 66 we expanded the chemical space to consider four kinds of dopants: anionic acceptors, cationic acceptors, anionic donors, and cationic donors. Only a single fixed dopant concentration and only the two smallest cluster sizes (Au monomers and dimers) were considered in this earlier study.…”
Section: Introductionmentioning
confidence: 99%
“…No matter which strategy is adopted to tune the electronic structure of the metal nanocatalyst, the nanometals are generally supported on an oxide substrate with a large specific surface area. In this scenario, interactions with the oxide support significantly impact the electronic structures and in turn the catalytic performance of nanometals [21,22]. Recently, we have demonstrated that the electron exchange between the two phases is highly correlated with the Fermi level of the oxide support [23].…”
Section: Introductionmentioning
confidence: 99%